Midterm Outcomes of 12 Renal Transplant Recipients Treated With Eculizumab to Prevent Atypical Hemolytic Syndrome Recurrence. Issue 12 (December 2017) - Levi, Charlène; Frémeaux-Bacchi, Véronique; Zuber, Julien; Rabant, Marion; Devriese, Magali; Snanoudj, Renaud; Scemla, Anne; Amrouche, Lucile; Mejean, Arnaud; Legendre, Christophe; Sberro-Soussan, Rebecca
Abstract : Background: Atypical hemolytic uremic syndrome (aHUS) is an orphan disease with a high rate of recurrence after kidney transplantation. However, reports of successful prevention of posttransplant aHUS recurrence with eculizumab emerged a few years ago. To further delineate its optimal use, we describe the largest series of kidney transplant recipients treated with prophylactic eculizumab. Methods: Twelve renal transplant recipients with aHUS-related end-stage renal disease received eculizumab: 10 from day 0 and 2 at the time of recurrence (days 6 and 25). Clinical and histological features, complement assessment, and free eculizumab measurements were analyzed. The median follow-up was 24.6 months. Results: Five patients had failed at least 1 previous renal transplant from aHUS. A genetic mutation was identified in 9 patients, anti-H antibodies were found in 2. No patient demonstrated biological recurrence of thrombotic microangiopathy under treatment. Three antibody-mediated rejections (AMRs) occurred without detectable C5 residual activity. AMR was associated with subclinical thrombotic microangiopathy in 2 patients. One patient lost his graft after several complications, including AMR. One patient experienced posttransplant C3 glomerulonephritis. The last median serum creatinine was 128.2 ± 40.8 μmol/L. Conclusions: These data confirm that eculizumab is highly effective in preventing posttransplantation aHUS recurrence, yet may not fully block AMR pathogenesis. Abstract : This small case series describes mid-term efficacy and safety of the use of eculizumab to prevent or treat atypical hemolytic-uremic syndrome recurrence after kidney transplantation, highlighting the difficulties in preventing antibody mediated reactions. Supplemental digital content is available in the text.